Optical Imaging of Mammary and Prostate Tumors in Living Animals using a Synthetic Near Infrared Zinc(II)-Dipicolylamine Probe for Anionic Cell Surfaces - Smith, Bryan A. (2010)
In vivo optical imaging shows that a fluorescent imaging probe, comprised of a near-infrared fluorophore attached to an affinity group containing two zinc(II)-dipicolylamine (Zn-DPA) units, targets prostate and mammary tumors in two different xenograft animal models. The tumor selectivity is absent with control fluorophores whose structures do not have appended Zn-DPA targeting ligands. Ex vivo biodistribution and histological analyses indicate that the probe is targeting the necrotic regions of the tumors, which is consistent with in vitro microscopy showing selective targeting of the anionic membrane surfaces of dead and dying cells. [Image: see text]